(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The immigration phenomenon has very significative socio economical implications that modify the welcome country’s economic, social, cultural, labour, etc scenery. The market, as far as it is formed by people with money and desires to buy, is being transformed by emergent and very diverse necessities of the multicultural groups. Thus, this article tries itself to make an approach to the characteristics of that new demand and to which are the opportunities that offer for the companies tooffer a marketing-mix specialized in this new market. In this sense a special referenceto the supply of the traditional market places is done, which they were in frank recession,because they have had to change from traditional supplies, towards places specializedin this type of consumers.